Особливості відтворення Шекспірової гри слів у перекладах Ірини Стешенко - Олексин, Ольга Зіновіївна; Oleksyn, O. Z. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті досліджено питання відтворення Шекспірової гри слів у перекладах І. Стешенко, яка посідає особливе місце серед перекладачів В. Шекспіра як автор найбільшої кількості українських перекладів – шести, серед яких чотири комедії («Венеціанський купець», «Багато галасу з нічого», «Комедія помилок», «Два веронці») та дві трагедії («Отелло», «Ромео і Джульєтта»). Проаналізовано основні методи перекладу та часто¬ту їх використання. Особливу увагу зосереджено на факторах, які впливають на методи перекладу гри слів, а саме: приналежність твору до жанру комедії чи трагедії, ідентифікація гри слів у тексті оригіналу, її тип, функції та перекладність загалом. The article focuses on rendering Shakespeare’s wordplay by I. Steshenko, who occupies a special place among Shakespeare’s translators as the author of the biggest number of translations – six, which include four comedies (“The Merchant of Venice”, “Much Ado About Nothing”, “The Comedy of Errors”, “The Two Gentlemen of Verona”) and two tragedies (“Othello, The Moor of Venice”, “Romeo and Juliet”). The paper analyses the main methods of wordplay translation and their frequency. A special attention is paid to the factors which influence wordplay translation methods, such as: genre characteristics of the play, wordplay identification in the text, its type, functions and translatability. I. Steshenko mainly resorts to formal and semantic transformations, therefore an original wordplay differs from a target wordplay. However, the translator tries to remain in a lexical and semantic field of a wordplay and preserve its functions. In general, I. Steshenko’s translations are performable and highly artistic from the viewpoint of the Ukrainian language but only partially equivalent as far as the rendering of wordplay is concerned.
Rendering Shakespeare’s Wordplay in Iryna Steshenko’s Translations
Keywords: Шекспірова гра слів; Shakespeare’s wordplay; методи перекладу гри слів; methods of wordplay translation; функції гри слів; wordplay functions